The berenstain bears' new pup eaudiobook - Berenstain, Jan (I Can Read, Level 1: Berenstain Bears., 2012)
Mama and the cubs take a trip to get some farm–fresh eggs, but they end up getting a farm–fresh pup! Now Brother and Sister have to learn to take care of Little Lady, the newest addition to the family. The Berenstain Bears' New Pup is a Level One I Can Read book, which means it's perfect for children learning to sound out words and sentences.